Addition of docetaxel to hormonal therapy in low- and high-burden metastatic hormone sensitive prostate cancer: long-term survival results from the STAMPEDE trial. (27th September 2019) - Clarke, N W; Ali, A; Ingleby, F C; Hoyle, A; Amos, C L; Attard, G; Brawley, C D; Calvert, J; Chowdhury, S; Cook, A; Cross, W; Dearnaley, D P; et al.
Abstract: Background: STAMPEDE has previously reported that the use of upfront docetaxel improved overall survival (OS) for metastatic hormone naïve prostate cancer patients starting long-term androgen deprivation therapy. We report on long-term outcomes stratified by metastatic burden for M1 patients. Methods: We randomly allocated patients in 2 : 1 ratio to standard-of-care (SOC; control group) or SOC + docetaxel. Metastatic disease burden was categorised using retrospectively-collected baseline staging scans where available. Analysis used Cox regression models, adjusted for stratification factors, with emphasis on restricted mean survival time where hazards were non-proportional. Results: Between 05 October 2005 and 31 March 2013, 1086 M1 patients were randomised to receive SOC ( n = 724) or SOC + docetaxel ( n = 362). Metastatic burden was assessable for 830/1086 (76%) patients; 362 (44%) had low and 468 (56%) high metastatic burden. Median follow-up was 78.2 months. There were 494 deaths on SOC (41% more than the previous report). There was good evidence of benefit of docetaxel over SOC on OS (HR = 0.81, 95% CI 0.69–0.95, P = 0.009) with no evidence of heterogeneity of docetaxel effect between metastatic burden sub-groups (interaction P = 0.827). Analysis of other outcomes found evidence of benefit for docetaxel over SOC in failure-free survival (HR = 0.66, 95% CI 0.57–0.76, P < 0.001) and progression-free survival (HR = 0.69, 95% CI 0.59–0.81, P < 0.001) with no evidence of heterogeneity of docetaxel effect between metastatic burden sub-groups (interaction P > 0.5 in each case). There was no evidence that docetaxel resulted in late toxicity compared with SOC: after 1 year, G3-5 toxicity was reported for 28% SOC and 27% docetaxel (in patients still on follow-up at 1 year without prior progression). Conclusions: The clinically significant benefit in survival for upfront docetaxel persists at longer follow-up, with no evidence that benefit differed by metastatic burden. We advocate that upfront docetaxel is considered for metastatic hormone naïve prostate cancer patients regardless of metastatic burden.